Comparability of Early Dynamic and Conventional Static Imaging With 18F-Fluorocholine PET/CT in a Patient With Primary Hyperparathyroidism. (November 2018) - Prabhu, Meghana; Kumari, Garima; Damle, Nishikant Avinash; Arora, Geetanjali; Tripathi, Madhavi; Bal, Chandrasekhar; Kumar, Praveen; Kumar, Rajeev
Abstract : Abstract: Recent studies have established the superiority of FCH PET/CT over MIBI scan in accurate preoperative localization of parathyroid adenomas. In this patient, we compared both early dynamic and conventional static imaging to see if early imaging could suffice. We describe a 15-year-old boy with primary hyperparathyroidism, in whom early dynamic FCH PET/CT was performed for 15 minutes after injection, followed by conventional static image at 60 minutes. Early dynamic images accurately localized the parathyroid adenoma. Also, higher SUVmax was observed on dynamic imaging when compared with conventional static images, but parathyroid-to-thyroid ratio was higher in the latter.